Do Social and Environmental Disclosures Increase Firm Value ? Evidence from Indian Companies - Charumathi, B.; Ramesh, Latha (Indian Journal of Finance, 2017)
There is a clear shift in the way the companies report their performance through the communications with their stakeholders. Moving from mere profit, the companies are increasingly showing their non-financial performance in terms of sustainability and social responsibility. Companies not only want to just spend on sustainability, but also like to project their activities to gain image among the stakeholders ; more often with a separate set of report called corporate sustainability report, which is based on the triple bottom-line (profit, people, and planet). This study focused on understanding the corporate social and environmental reporting trends of Indian non-financial companies and the impact on market valuation. The sample constituted of companies in the BSE-100 index and data for 5 financial years - from FY2010 to FY2014 - were used. This period was chosen as it witnessed several regulatory changes in the triple bottom line reporting in the form of new Companies Act, 2013 and Clause 55 of the listing agreement. Paired 't' test and panel data regression model were used for analyzing the data. This study found that the level of social and environmental disclosures has significantly improved post business responsibility reporting and positively significantly influenced market valuation.